KONTRIBUSI DISPOSISI MATEMATIS DAN METAKOGNISI TERHADAP HASIL BELAJAR MATEMATIKA SISWA: CONTRIBUTION OF MATHEMATICAL DISPOSITION, METACOGNITION ON MATHEMATICS LEARNING ACHIEVEMENT STUDENTS - Thalib, Ahmad; Rusli; Syarifatunnisa (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
The purpose of this study was to determine how big the contribution of mathematical disposition and metacognition to students’ mathematics learning outcomes is. The approach used is quantitative. The research type is ex-post-facto. The populations were all eighth-grade students of SMP Negeri 3 Sungguminasa, Gowa Regency with a total sample of 105 students who were taken using the cluster random sampling technique. Collecting data using a questionnaire instrument and a test of mathematics learning outcomes. The data analysis technique used is descriptive analysis and inferential analysis (linear regression analysis). The conclusion of this research is: (1) the contribution of mathematical disposition of 0.4% to learning outcomes while the other 99.6% were other variables not examined; (2) the contribution of 4.6% metacognition on learning outcomes while the other 95.4% are other variables that are not studied at; (3) the contribution of mathematical disposition and metacognition simultaneously was 5.1% on students’ mathematics learning outcomes while the other 94.9% were other variables not examined; (4) mathematical disposition has a positive influence on the mathematics learning outcomes of class VIII students; (5) metacognition has a positive effect on students’ mathematics learning outcomes which can be seen in the equation Y=0.071X1+0.216X2+0.97 which illustrates that an increase in one unit of Y will increase X1 by 0.071 and X2 by 0.216.